SIZING AND EXPERIMENTAL STUDY OF A SOLAR STILL FOR THE PRODUCTIVITY OF WATER DESALINATION IN SOUTH-WEST OF ALGERIA – BECHAR: التصميم والدراسة التجريبية لجهاز التقطير الشمسي لإنتاجية تحلية المياه في جنوب غرب الجزائر – بشار - Abdelkarim Maamar Abdelkader, Bounegta Bachir Mohammed, (Journal of engineering sciences and information technology, 2020)
Algeria, like many countries belonging mostly to the Third World, has considerable water resources saline (salt content ranging between 1500 and 2000 ppm, exceeding the required standards for drinking water and therefore unfit for consumption). We must therefore think of making use these huge reserves interested in desalination techniques. The stain majored is therefore to achieve a distiller solar plan which meets these needs in drinking water. The absorber surface of the modified solar still is coated with black enamel paint and covered with copper chips. The evaporation rate of the water in the solar still is directly proportional to the exposure area of the water. Thus the productivity of the solar still increases with the free surface area of the water in the basin. The distillate yield was found to have improved considerably, especially when the water depth was high. The study also indicated some design features that would further enhance the improvement in output due to the modification made, the evaporation rate is proportional to the temperature of the free surface area of the water only. A general model based on heat transfer balances in each component of the system was developed to predict the mass of freshwater. The efficiency of this still was about 65% and can produce about 5.13 l/m2 per day, experimental studies and the outcomes are discussed in the article. We propose a new design of the cascading solar desalination still with obstacles and preheating of inlet water.